Peran Corporate Social Responsibility sebagai Moderasi Pengaruh Green Employee Behavior terhadap Sustainable Performance - Pramiana, Omi; Putri, Syafira Anindya (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to examine the influence of Green Employee Behavior (GEB) on Sustainable Performance (SP) in Micro, Small, and Medium Enterprises (MSMEs) in Jombang Regency, with a focus on the moderating role of Corporate Social Responsibility (CSR). The population of the study consists of 4,095 wastegenerating MSMEs, with a sample of 98 MSMEs selected using the Slovin formula. Primary data were collected through questionnaires based on a Likert scale and analyzed using WarpPLS 8.0 software. The results indicate that green employee behavior has a significant positive impact on sustainable performance, encompassing customer growth, asset development, and work planning. Furthermore, corporate social responsibility significantly moderates this relationship, but its effect becomes negative when it prioritizes external image over supporting internal initiatives.